2021
DOI: 10.1186/s13756-020-00879-3
|View full text |Cite
|
Sign up to set email alerts
|

Core components of infection prevention and control programs at the facility level in Georgia: key challenges and opportunities

Abstract: Background The Georgia Ministry of Labor, Health, and Social Affairs is working to strengthen its Infection Prevention and Control (IPC) Program, but until recently has lacked an assessment of performance gaps and implementation challenges faced by hospital staff. Methods In 2018, health care hospitals were assessed using a World Health Organization (WHO) adapted tool aimed at implementing the WHO’s IPC Core Components. The study included site asse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 33 publications
3
23
1
Order By: Relevance
“…26 Gaps in the effective implementation of IPC training programmes have also been highlighted by other single-country IPCAF surveys. 23,25 In our study, very few facilities in low-income countries had access to a full-time IPC professional and significantly lower scores were found for core components 1 and 2, indicating defective IPC programmes and limited availability of guidelines. Efforts to build or participate in recognised IPC certification pathways should be strongly encouraged, such as the training programmes offered by the European Committee on Infection Control and the Infection Control African Network.…”
Section: Income Levelmentioning
confidence: 55%
See 2 more Smart Citations
“…26 Gaps in the effective implementation of IPC training programmes have also been highlighted by other single-country IPCAF surveys. 23,25 In our study, very few facilities in low-income countries had access to a full-time IPC professional and significantly lower scores were found for core components 1 and 2, indicating defective IPC programmes and limited availability of guidelines. Efforts to build or participate in recognised IPC certification pathways should be strongly encouraged, such as the training programmes offered by the European Committee on Infection Control and the Infection Control African Network.…”
Section: Income Levelmentioning
confidence: 55%
“… 23 In our study, HAI surveillance and monitoring and feedback of IPC practices scored lowest among low-income countries, similar to the study in Pakistan and another study in Georgia among 41 hospitals using an adapted version of the IPCAF. 23 , 25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was indeed highlighted by participants in this phase of this study. Another study by Deryabina et al (2021) used the WHO IPC core components to perform an assessment of IPC practice across 41 hospitals in Georgia. They also reported that most IPC programmes were not comprehensive and that they did not articulate clear objectives, workplans, targets or budgets.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, IPC staff shortages prevented regular education to be delivered. A recent study by Deryabina et al (2021) used the WHO IPC core components to perform an assessment of IPC practice across 41 hospitals in Georgia. They also found that IPC education provided for healthcare professionals was considerably variable, inconsistent, and inadequate in that it did not result in improved staff knowledge and patient outcomes.…”
Section: Discussionmentioning
confidence: 99%